THE COST OF SOLIDARITY: THE SALVADORAN LABOR MOVEMENT IN PUERTO EL TRIUNFO AND GREATER SAN SALVADOR IN 1979 AND 1980 - Gould, Jeffrey L. (2015)
This essay analyzes the labor movement in Puerto Triunfo and Greater San Salvador during 1979 and 1980. The shared ideological foundation between both was a rudimentary form of syndicalism lacking formal organization at local or national levels. The evidence suggests that while these movements echoed some elements of classical syndicalism—such as attitude, technique, and strategy—they lacked its underlying hope. These ideological forms remained inchoate. Salvadoran syndicalists operated under harsh, authoritarian, and increasingly violent conditions, facing arrests, torture, and assassinations. Such repression forced semi-clandestine action, making the realization of grassroots democracy—essential to syndicalism—extremely difficult. The tensions between syndicalist ideals and their actual expressions in both the port and the capital led to misunderstandings and alienation among different labor groups. However, these dialectical tensions—between formal and informal discourse, leadership and base, periphery and center—also fueled the growth and radicalization of the labor movement. This essay traces these broader transformations while offering a detailed study of the political and social shifts in Puerto El Triunfo. Though distinct in context, this local history both reflected and influenced the larger labor movement in El Salvador. The concept of desencuentro is used to interpret the disconnects and contradictions shaping these developments.